2020
DOI: 10.1016/j.ajog.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Can postpartum pelvic floor muscle training reduce urinary and anal incontinence?

Abstract: BACKGROUND: Pelvic floor dysfunction, including urinary and anal incontinence, is a common postpartum complaint and likely to reduce quality of life. OBJECTIVE: To study the effects of individualized physical therapisteguided pelvic floor muscle training in the early postpartum period on urinary and anal incontinence and related bother, as well as pelvic floor muscle strength and endurance. MATERIALS AND METHODS: This was an assessor-blinded, parallel-group, randomized controlled trial evaluating effects of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 23 publications
2
101
0
2
Order By: Relevance
“…Improvement in the quality of life and/or a reduction in the severity of symptoms has been observed both in patients with idiopathic FI [ 47 ], with FI of different etiologies [ 61 ], and with fecal incontinence associated with scleroderma [ 60 ]. A positive effect of BF therapy has also been noted in patients after childbirth complicated by damage to the sphincters [ 52 , 58 ]. BF training has been demonstrated to be effective both in the model of pre- or post-FI surgery due, for example, to damage to the sphincters [ 50 , 51 ], as a stand-alone therapy in moderate FI [ 60 ], and in the prevention of FI [ 49 ].…”
Section: Physiotherapeutic Techniques For the Treatment Of Fecal Imentioning
confidence: 99%
“…Improvement in the quality of life and/or a reduction in the severity of symptoms has been observed both in patients with idiopathic FI [ 47 ], with FI of different etiologies [ 61 ], and with fecal incontinence associated with scleroderma [ 60 ]. A positive effect of BF therapy has also been noted in patients after childbirth complicated by damage to the sphincters [ 52 , 58 ]. BF training has been demonstrated to be effective both in the model of pre- or post-FI surgery due, for example, to damage to the sphincters [ 50 , 51 ], as a stand-alone therapy in moderate FI [ 60 ], and in the prevention of FI [ 49 ].…”
Section: Physiotherapeutic Techniques For the Treatment Of Fecal Imentioning
confidence: 99%
“…Pain, specifically low back pain, has been associated with urinary incontinence in large epidemiological studies [ 40 ]. Thirty percent of postpartum mothers experience urinary incontinence and 10% experience anal incontinence [ 41 ] as pregnancy and parity are well known causes of pelvic floor dysfunction [ 42 ]. Participating in a sport, specifically one with high impact such as running, is also a risk factor for incontinence [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…When muscle strength and pelvic floor support are abnormal, UI is prone to occur. Some researchers reported that during pregnancy and postpartum pelvic floor muscle training improved muscle strength and endurance and decreased the rate of UI 17,18 19 …”
Section: Discussionmentioning
confidence: 99%